Evaluation of pear (Pyrus communis) sucker for different root stock characters - Srivastava, K K; Das, Biswajit; Sundouri, A S; Sharma, M K; Singh, S R (The Indian Journal of Agricultural Sciences, 2008)
A study was conducted during 2002-06 to standardize selection of mother tree and to identify composite mother trees with desirable parameters for sucker selection of pear (Pyrus communis L.). Thorny- and spreading-type suckers were of dwarf stature with less intemodal length, while thorn density was more in erect growing sucker. ’William Bartlett’ cultivar when budded on V15 sucker showed good physical graft compatibility (least variance 0.91), followed by ’Vicar of Winkfield’ on V33 suckers (1.13 variance). Significantly maximum fruiting spurs/plant (6.30) was observed in ’William Bartlett’ on V11, and least (1.30) on ’Kainth’. However, ’William Bartlett’ when budded on V11 sucker gave the maximum (43%) plants in fruiting and ’Vicar of Winkfield’ when was raised on ’Kainth’ the least (23%) plants in fruiting.